Effect of chitosan and polyethylene glycol as plasticizer improves the physical, mechanical, moisture, and thermal properties of films for food packaging - Nur Nadiah, Che Aziz; Fatmawati, Adam; Nurul Aini, Mohd Azman; Nur Hidayah, Mat Yasin (AIP Publishing, 2025)
The objective of this research was to formulate chitosan (CS)-based films by addition of plasticizers to produce environmental friendly bioplastic and investigated the physicochemical outcome and functional performance of chitosan-based films. In this study, medium molecular weight of chitosan and polyethylene glycol (PEG) were prepared by using the solvent casting technique. The effect of chitosan blended with different amount of PEG (0, 0.5, 1.0, 1.5, 2.0, and 2.5 ml) on physical, moisture, mechanical, and thermal properties were evaluated by the thickness, tensile, elongation at break, water contact angle, moisture content, and thermogravimetric analysis (TGA). The incorporation of PEG to chitosan film reduced the brittleness and fragility of films. The films composed on chitosan and 1.5 ml of PEG exhibited the best mechanical properties with 46.94 N for tensile strength, while the percentage of elongation at break was 60%. The viscosity, shear stress, film thickness, and moisture content increased in response to an increase in PEG amount, whereas contact angle decreased. As the amount of PEG in the chitosan films increased, the plastic like behaviour of the films was disappeared and they eventually developed a flexibility and persistent structure with 23.22% and 83.87% for moisture content and contact angle, respectively. The PEG-plasticized films demonstrated higher thermal stability in comparison to pure film. The conclusion of this research shed light on the production of bioplastic food packaging.